Using Blockchain Technologies in the Digital Economy - ugli, Davronov Kilichbek Firdavs (European Journal of Life Safety and Stability (2660-9630), 2022)
Ultimately, bitcoin has become so popular that it combines the three functions of money, and then becomes just as important as the dollar. Despite the negative image in society and regulatory restrictions, it cannot be said that the external environment is hindering the prosperity of cryptocurrencies.